Neural Stem Cell Niches: Critical Roles for the Hyaluronan-Based Extracellular Matrix in Neural Stem Cell Proliferation and Differentiation - Preston, Marnie (2011)
Neural stem/progenitor cells capable of differentiating into the neurons and glial cells that populate the mammalian central nervous system (CNS) persist in specific neural stem cell niches that regulate stem cell proliferation, survival and differentiation. There is growing evidence that the extracellular matrix within neural stem cell niches is required for neural stem cell maintenance. Here, we review findings supporting a pivotal role for the glycosaminoglycan hyaluronan (HA) and its transmembrane receptors in neural stem/progenitor cell proliferation, differentiation and maturation. We also outline findings supporting changing roles for HA as cells become committed to distinct lineages in the brain and spinal cord.